2006
DOI: 10.1128/mcb.26.2.535-547.2006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sexual Dimorphism: Mutational and Chemogenetic Analysis of the Doublesex DM Domain

Abstract: Doublesex (dsx) is a transcription factor in Drosophila that regulates somatic sexual differentiation. Maleand female-specific splicing isoforms of DSX share a novel DNA-binding domain, designated the DM motif. Broadly conserved among metazoan sex-determining factors, the DM domain contains a nonclassical zinc module and binds in the DNA minor groove. Here, we characterize the DM motif by site-directed and random mutagenesis using a yeast one-hybrid (Y1H) system and extend this analysis by chemogenetic complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 72 publications
(94 reference statements)
1
25
0
Order By: Relevance
“…These residues participate in two intertwined Zn 2+ -binding sites [27]. The mutagenesis test in the DM domain of dsx in Drosophila demonstrated that these eight motif-specific histidines and cysteines that are engaged in zinc coordination are all critical and are not interchangeable [26].…”
Section: Discussionmentioning
confidence: 99%
“…These residues participate in two intertwined Zn 2+ -binding sites [27]. The mutagenesis test in the DM domain of dsx in Drosophila demonstrated that these eight motif-specific histidines and cysteines that are engaged in zinc coordination are all critical and are not interchangeable [26].…”
Section: Discussionmentioning
confidence: 99%
“…First, Dam alone was used to measure non-specific methylation (van Steensel and Henikoff, 2000). As the fly genome contains 'transcription factor colocalization hotspots', where transcription factors accumulate through protein-protein interactions (Moorman et al, 2006), a second control was Dam fused to a DSX protein with a mutation in its DNA-binding domain (R91Q) that has lost the ability to bind 2763 RESEARCH ARTICLE DSX targets and the evolution of sex the Yp1 DSX-binding site (Erdman and Burtis, 1993;Zhang et al, 2006). R91Q-Dam should bind to transcription factor hotspots, but not to real DSX-binding sites.…”
Section: Whole Genome Identification Of Dsx-binding Regionsmentioning
confidence: 99%
“…An amino acid substitution at Y67F was found in both sexes of B. dorsalis, B. correcta, and B. tryoni. This amino acid change was identified as being tolerant of amino acid substitutions (Zhang et al, 2006). Likewise, the amino acid changes at both positions 72 and 101 in OD1 can be different in males and females of B. correcta, because they might be selectively neutral polymorphisms.…”
Section: Resultsmentioning
confidence: 99%